TREINAMENTO RESISTIDO FRENTE À SARCOPENIA UMA FORMA DE PROPOCIONAR UMA MELHOR QUALIDADE DE VIDA AO IDOSO (REMUNOM, 2024)
The percentage of the elderly population in society has increased more and more in recent years and it is estimated that by the year 2025 this population will reach up to about 1.2 billion people over 60 years old in the world. And in aging, there is a regression in the physiological systems, and consequently common at this stage of life and associated with lack of physical activity, loss of muscle mass, generates a decrease in muscle strength as a consequence. The decrease in strength is directly associated with the health and quality of life of this population. So the goal of this study was to prove the importance of resistance training to reduce the detrimental effects that ultimately lead to this early complication of sarcopenia. The study was carried out through literary researches, comprised of scientific articles from the sky and academic google, since they allow and cover a much wider range of cases, it is verified that the resistance exercise allows freedom and well-being and consequently improving the quality of life of the elderly, preventing in the possible way the harmful effects that eventually lead this population to sarcopenia.